Sistem Photovoltaic (PV) Di Gedung ITS PKU Muhammadiyah Surakarta - Wahyu Priyono; Eko Nugroho; Setyo Adi Nugroho (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
To support green energy and reduce the effects of greenhouse gases, it is necessary to conceptualize and explore the use of renewable energy. In this research, the use of new renewable energy, especially photovoltaics (PV), will be applied to educational buildings, especially at ITS PKU Muhammadiyah Surakarta. This system is intended to reduce the use of conventional electrical energy. This system will be installed on the roofs of campus buildings with installation plans to meet the power requirement of 4.8 kW. This photovoltaic (PV) system will be modeled to determine the number of PV panels needed. Based on the simulation results, the number of panels required is 36 panels (2 series, 18 parallel) to produce 4.85kWh of power. Modeling and analysis of this system was carried out using RETScreen and MATLAB SIMULINK software.